"Animula, vagula, blandula", o sobre el alma perdidas de los animales - Cragnolini, Monica Beatriz (2015)
This paper analyses a frame of the history of Western Thought in which the issue of animals soul and feeling arises. This paper shows how in Antoniana Margarita, a Gómez Pereira?s work, the animal is considered from the point of view of human needs (too human needs, as Nietzsche would say). The question is how it became necessary to deprive animals of soul, in order to use them for production, experimentation and performance (in zoos, circuses, etc)